The Impact of Game Avatar Customization in Improving User Experience and Gamer Loyalty: Experiment in Role Playing Game (RPG) Based Video Game - Damar Kristanto (Universitas Airlangga, 2018)
The increasing number of video game titles raises competition between video game developers getting tighter and more competitive, this encourages the game developers to be more creative in designing their games so that players become loyal to play and not quickly switch to playing other games. While we know that game development is very difficult, time consuming and requires a lot of costs for the RPG genre. So that the loyalty of game players in playing games becomes a crucial problem.This study aims to explain how the customization of game avatars can increase the loyalty of video game players in playing role-playing games (RPGs).This study uses the within-subject experimental method with participants who are RPG video game players who have played for at least 1 year, 24 participants participated in the 8 experiment session throughout the study. The results of this study indicate that avatar customization is very important because it can improve the player's self-identification in the game, improve the playing experience, improve the perceived quality of the video game played, increase the flow and immersion of players, and increase gamer loyalty. Another result that was raised was that the use of avatars that were the same gender with players (male players using male avatars) did not have higher flow and immersion than when using different genders (male players use female avatars) so that this raises new issues of gander swapping in the role playing video game that can be continued for further research.